Hubungan Kesiapan Pembelajaran Online (E-Learning Readiness) Dengan Burnout Akademik Di Masa Pandemi COVID-19 Pada Mahasiswa Stikes Siti Hajar Medan - Nurul Aini (Jurnal Kesehatan dan Fisioterapi, 2021)
Abstract− The case of the corona virus (COVID-19) was declared by WHO as a HEIC (public health emergencies international concern). A circular letter was issued by the Minister of Education and Culture of the Republic of Indonesia to divert the way students and students learn online (e-learning). In the process of online learning (e-learning) often appears pressure and stress on students who carry it out. Burnout is one type of psychological disorder due to learning stress that appears in almost all schools. So the purpose of this study was to determine the relationship between online learning readiness (E-learning readiness) and academic burnout during the COVID-19 pandemic for Stikes Siti Hajar Medan students. The analysis technique used in this study is a simple regression analysis technique, with a sample size of 99. The results of this study indicate the value of F = 5.241 where P <0.05, with a correlation coefficient of -0.217. It can be interpreted that the e-learning readiness variable has a significant negative relationship with academic burnout. the higher the e-learning readiness, the lower the academic burnout, conversely the lower the e-learning readiness, the lower the academic burnout Keywords: Student, Academic Burnout, E-Learning Readiness.